Effectiveness of spontaneous ovulation as monitored by urinary luteinising hormone versus induced ovulation by administration of human chorionic gonadotrophin in couples undergoing gonadotrophin‐stimulated intrauterine insemination: a randomised controlled trial. (19th July 2019) - Thomas, S; Sebastian, T; Karthikeyan, M; Mangalaraj, AM; Aleyamma, TK; Kamath, MS
Abstract : Objective: To compare effectiveness of spontaneous ovulation monitored by urinary luteinising hormone (LH) versus induced ovulation by administration of human chorionic gonadotrophin (hCG) in couples undergoing gonadotrophin‐stimulated intrauterine insemination (IUI). Design: Randomised controlled trial. Setting: University‐level infertility unit. Population: Couples with unexplained infertility, mild endometriosis, mild male factor infertility and polycystic ovarian syndrome. Methods: Couples were randomised to an LH group (Group A), in which urinary LH was measured daily to detect spontaneous ovulation, or an hCG group (Group B), in which urinary hCG was administered as a trigger. Main outcome measures: Clinical pregnancy rate. Secondary outcomes – ongoing pregnancy, live birth, multiple pregnancy and miscarriage rates. Results: A total of 392 couples were randomised with 196 in each arm. The clinical pregnancy rate per woman randomised was 14/196 (7.1%) in the LH arm versus 15/196 (7.6%) in the hCG arm ( P = 0.847, which was not statistically significant). Similarly, the ongoing pregnancy rates [13/196 (6.6%) versus 14/196 (7.1%); P = 0.84] and the live birth rates [13/196 (6.6%) versus 14/196 (7.1%); P = 0.84] between the two groups did not show any significant difference. The duration of stimulation and gonadotrophin dosage also did not differ significantly between the two methods. Conclusion: There was no significant difference in clinical pregnancy rates when urinary LH and hCG trigger were compared as methods to time insemination in women undergoing gonadotropin‐stimulated IUI. Tweetable abstract: A randomised controlled study showing similar effectiveness between two different methods of timing IUI. Tweetable abstract: A randomised controlled study showing similar effectiveness between two different methods of timing IUI.